In the light of evolution - Avise, John C.; Ayala, Francisco Jose , 1934- (Sackler Colloquium series, 2008)
Presents modern scientific perspectives on the evolutionary origin and maintenance of complex phenotypes including various behaviors, anatomies, and physiologies. This book includes 14 papers presented by distinguished evolutionists at the colloquium.